Predictive value of vascular endothelial growth factor receptor type 2 in triple-negative breast cancer patients treated with neoadjuvant chemotherapy - Babyshkina, Nataliya; Zavyalova, Marina; Tarabanovskaya, Natalia; Dronova, Tatyana; Krakhmal, Nadejda; Slonimskaya, Elena; Kzhyshkowska, Julia; Choynzonov, Evgeny; Cherdyntseva, Nadejda (Molecular and cellular biochemistry, 2017)
The identification of informative biomarkers that could predict the treatment response is particularly important in the triple-negative (TN) breast cancer, which is characterized by biological diversity. The aim of this study was to investigate the impact of vascular endothelial growth factor receptor (VEGFR2) expression and its gene polymorphisms on pathologic complete response (pCR) to neoadjuvant chemotherapy (NCT) in Russian patients with TN breast cancer. We performed a retrospective analysis of 70 women with operable TN breast cancer, who underwent NCT with 5-fluorouracil, adriamycin, and cyclophosphamide (FAC) or cyclophosphamide, adriamycin, and capecitabine (CAX) between 2007 and 2013. VEGFR2 expression was evaluated before NCT by immunohistochemistry. TaqMan SNP assays were used for genotyping KDR − 604T>C (rs2071559) and KDR 1192G>A (rs2305948) polymorphisms. The pCR was used as an end-point in the treatment efficacy analysis. In the univariate analysis, the pCR rate was strongly associated with young age (P = 0.004), high Ki67 expression (P = 0.012), lymph node negativity (P = 0.023) as well as with positive VEGFR2 expression (P = 0.019) and the CAX regimen (P = 0.005). In the multivariate analysis, only patient’s age (P = 0.005) and pre-NCT VEGFR2 expression (P = 0.048) remained significant predictors of pCR. The pCR rate was higher in the CAX-treated patients than that in the FAC-treated patients (P = 0.005). Our results revealed that − 604TT genotype of rs2071559 and age < 50 years were correlated with a pCR in the CAX-treated patients. VEGFR2 expression in pre-NCT tumors and KDR gene polymorphism can be considered as additional predictive molecular markers of pCR in Russian TN breast cancer patients treated with NCT.
First published: 11 December 2017